Novel power electronic multilevel converters - Ding, Wenyuan (Nanyang Technological University, 2022)
The classic NNPC converter has the problem of large voltage fluctuation across the flying capacitor. To deal with this problem, this paper proposes an improved ANNPC 5-level converter. A finite control set model predictive control (FCS-MPC) approach for the proposed new converter system is designed to achieve accurate tracking of the output current and voltage balance across the flying capacitors. The proposed new ANNPC converter has the advantages of small flying capacitor voltage ripple and less optimization targets, which can be widely used in photovoltaic power generation systems. Finally, experimental results in multiple cases verify the effectiveness of the proposed novel converter.